APPLICATION OF CLING FILM OVER BURN WOUNDS (OCCLUSIVE WOUND DRESSING): OUR EXPERIENCE - Abidin, Zain ul; ilyas, Asma; Khalid, Farrukh Aslam; Mehrose, Muhammad Younas; Shahzad, Imran; Mujahid, Abdul Malik; Alam, Muhammad Amin; Tarar, Moazzam Nazeer (Journal of Ayub Medical College Abbottabad, 2021)
Background: This study shares our experience and review the outcome of the use of cling film with silver sulfadiazine cream in terms of healing time, and patient’s satisfaction score. Methods: It was a descriptive case series conducted at Jinnah Burn and Reconstructive Surgery Center, Lahore, from March 2018 to February 2019. In this study, a thick layer of silver sulfadiazine was applied and then wrapped with cling film on 35 patients sustained mix thickness burns on the trunk and limbs. Dressing was done daily after wound wash with normal saline. Consultant Plastic surgeon assessed the wound healing by observation and serial photographs. Duration of wound healing and complications were noted. Results: Complete wound healing was achieved in 25 (71.4%) patients with mean healing time of 13.3 days (range 11-15 days). The wound infection was seen in 5 (14.2%) patients, that were diagnosed by change in colour of wound edges and patients with signs of sepsis (ABA scoring). Sepsis was treated in 5 patients with debridement and culture specific antibiotics. split skin graft done in 8 (22.8%) cases Conclusion: Moist wound dressing with Silver Sulfadiazine and cling film is cost effective, easy to apply with good visibility of the wound and has good patient satisfaction, but is labour intensive.